FAKTOR PENDUKUNG DAN PENGHAMBAT DALAM PROSES PERUBAHAN ORGANISASI PADA POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA - Utama, Nang Randu (LPPM Universitas Terbuka, 2017)
This study aims to obtain a description of the supporting and inhibiting factors in the process of organizational change of education based on management perspective that occurs in the scope of higher health education of the Ministry of Health of the Republic of Indonesia. This study used a qualitative approach by conducting case study at Palangka Raya Health Polytechnic. The research results are as follows: (a) Supporting factor that must be there is the existence of a manual or technical guidance in organizing the organization; (b) Whereas the inhibiting factor is the old habits, the mindset, the mental model is still inhibiting from the organizers and members of the organization; (c) The inhibiting factor is the existence of selfishness of each highly visible party; (d) Inhibitors may also occur if there are still